Adoção da tecnologia da informação na pecuária de corte - Machado, João Guilherme de Camargo Ferraz (2007)
Information Technology (IT) starts to play an important role in the day-by-day, changing the way the cattlemen manage their properties. IT affects business management as it allows for search, access, storage and dissemination of information, improving the decision-making process. Besides softwares and agribusiness websites, IT includes electronic devices for storage of sanitary, nutricional and genetic information; television channels and telecommunications structure. This research aimed to study the use and the diffusion of IT in the beef cattle breeding, from the analysis of the factors that have influenced its adoption; to describe resources, procedures and necessary actions for IT operation; to segment (classify) rural enterprises by their technological level; and to elaborate suggestions to intensify the IT uses in the cattle breeding business. The research was performed in two stages, quantitative and qualitative. In the first stage, a survey with producers was performed. Information concerning the different technologies adopted and the attitudes taken with IT, enabled to identify the level of innovativeness of producers. It was possible to classify them by the similarities of the technological position. The second stage analyzed experiences, opinions and perspectives regarding the technology integrated to the productive system. Two properties were analyzed by each category, totalizing ten case studies, by personal interviews. The results indicated the reasons of the adoption or rejection of a certain IT by the producers, allowing for the identification of the reasons why some producers have adopted it more quickly than others. It was possible to understand the modifications in the rural organization due to IT adoption, as, for example, improvement in managerial skills. Altogether, the processes have been improved and became easier, with positive consequences in several areas, including human resources and the enterprise s image in the market.